Utilizing Digital Platforms to Promote Floating Markets of Banjarmasin: A Case for Sustainable River Tourism Development (Journal of Wetlands Environmental Management, 2024)
The floating markets of Banjarmasin represent a vital cultural attraction in South Kalimantan, yet they encounter challenges in balancing modernization with sustainability. This study examines the role of digital platforms such as social media, websites, and mobile applications in promoting sustainable tourism at these markets. Utilizing a Systematic Literature Review (SLR) approach, the paper analyzes existing research on the effectiveness of digital tools in enhancing tourist engagement, expanding market visibility, and encouraging environmentally responsible tourism. The findings indicate that digital platforms can boost the visibility of Banjarmasin’s floating markets, attract a broader spectrum of visitors, and support sustainable tourism practices. Nevertheless, significant challenges persist, particularly regarding the integration of local communities and the preservation of the river ecosystem. This study underscores the necessity for digital strategies that align with sustainability principles, ensuring tourism benefits for both the local economy and the environment. The review offers insights for tourism operators and policymakers on leveraging digital branding to advance sustainable river tourism development in Banjarmasin, and provides practical recommendations for future growth.